KARAKTERISTIK SIFAT MEKANIK DAN STRUKTUR MIKRO PADA MATERIAL Sn-0,7Cu-“X”Zn - Ridwan Adidarma; Erwin Siahaan; Abrar Riza (Program Studi Teknik Mesin Universitas Tarumanagara, 2017)
Abstract: Lead (Pb) in solder has been used for decades in industries of electronic equipment. Mostly in the lead solder old electronic equipment containing 63% (Sn), 37% lead (Pb). Heating solder in high temperature steam generating heat which can damage the respiratory system. The purpose of this analytic is to obtain the characteristics of the mechanical properties of the alloy Sn-0,7Cu-